Validation of 2004 ISMP medication safety self assessment tool for use in Philippine Military Hospital - Lim, Ma. Dolores M.
Background of the study: Medication error is considered as one of the major problem of the healthcare system. Several programs have been adopted to promote medication safety such as computerization, use of bar coding, pharmacist participation etc. In the United States of America they use the 2004 ISMP Medication Safety Self Assessment for Hospitals to help assess the medical practices of hospitals and identify opportunities for improvement. However, in the Philippines medication safety self-assessment is not a regular part of the programs of the hospital. Likewise, there is no existing tool that would assess medication safety in hospitals in the Philippines. There is a potential for using this tool in local hospitals here but its validity, applicability and feasibility still need to be tested.